Emotional and Behavioral Changes in Older Adults With High Risk of Cognitive Impairment During the COVID-19 Pandemic - Fu, Jiangning; Liu, Xiaomei; Li, Jing; Ma, Zhuoya; Li, Juan (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) is not only a threat to physical health but also a stressor to mental health, particularly for older adults. Previous studies have indicated that healthy older adults have resilience to cope with such stressful event through emotional and behavioral effort. However, very few have investigated the coping ability of older adults with High Risk of Cognitive Impairment (HRCI), as they are characterized with risk factors that can make them more vulnerable to COVID-19 in both physical and mental aspects. To examine whether older adults with HRCI were able to cope with and recover from the outbreak of COVID-19, we investigated the changes of their self-reported emotional states and intentions of taking protective behaviors between the outbreak period (data collected from February 17th to 24th, 2020) and the remission period (data collected from April 7th to 20th, 2020). The results showed that compared with the outbreak period, older adults with HRCI showed better emotional states and higher levels of intention to take more protective behaviors during the remission period. Subgroup analysis showed that even those who showed relatively poor coping abilities during the outbreak period could gradually improve their emotional states and intend to take more protective behaviors later on in the remission period. Therefore, these results suggested that older adults with HRCI were able to cope with and recover from the pandemic outbreak.